2010
DOI: 10.3402/ijch.v69i2.17432
|View full text |Cite
|
Sign up to set email alerts
|

Unnatural deaths in reindeer-herding Sami families in Sweden, 1961–2001

Abstract: Objectives. Unnatural deaths among Indigenous populations, including the Swedish Sami, occur more often than among the general population. To find prevention strategies, we explored the circumstances of the unnatural deaths of members of reindeer-herding Sami families. Study design. The number of deaths from among a cohort of 7,482 members of reindeer-herding Sami families were retrieved from the National Board of Health and Welfare for the years 1961- 2001.Methods. An evaluation of the information from autops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
(21 reference statements)
0
14
0
1
Order By: Relevance
“…Communicating negative feelings and thoughts may be a protecting act helping to understand and regulate feelings and behaviours, thus, instead of interpreting the higher prevalence of negative feelings in women as vulnerability, it could be a strength helping women to solve conflict and adapt to different circumstances in order to “survive”. For instance, even if depression is twice as common in women, men more often commit suicide and, are more often involved in fatal accidents than women (36,37). …”
Section: Discussionmentioning
confidence: 99%
“…Communicating negative feelings and thoughts may be a protecting act helping to understand and regulate feelings and behaviours, thus, instead of interpreting the higher prevalence of negative feelings in women as vulnerability, it could be a strength helping women to solve conflict and adapt to different circumstances in order to “survive”. For instance, even if depression is twice as common in women, men more often commit suicide and, are more often involved in fatal accidents than women (36,37). …”
Section: Discussionmentioning
confidence: 99%
“…The Swedish Causes of Death Register was used to examine life expectancy and specific causes of death among reindeer-herding and non-reindeer-herding Swedish Sami over the period 1961–2000 (1417). No difference in life expectancy was observed between the Sami and the non-Sami population of the same geographic region.…”
Section: Mortality and Diseasesmentioning
confidence: 99%
“…Detailed analyses of all unnatural death that occurred among reindeer-herding men between 1961 and 2001, using autopsy records at the National Board of Forensic Medicine, police reports, and medical records at the County Council, showed that suicides contributed to 23% of all deaths, road traffic accidents to 16%, and snowmobile fatalities to 11% (17). Half of the victims tested positive for alcohol, and alcohol abuse was documented in 15% of the victims.…”
Section: Mortality and Diseasesmentioning
confidence: 99%
See 2 more Smart Citations